Mapping Regions of Provenance for Italy - Fulvio Ducci; Luisa Maria Cagelli; Paolo Camerano; Lorenzo Camoriano; Immacolata Librandi; Giuseppe Pignatti; Alessandra Stefani (Annals of Silvicultural Research)
In the follow-up of 1999/105/CE Directive on national level, the new map of regions of provenance for forest reproductive materials of Italy is adopted as reference for the national register of forest basic materials. The new map was outlined to match needs linked to the transposition of European legislation to the complexity of the Peninsula’s environment and the national nursery system. The main objective in this technical note is to present the map units in relation to the distribution of main forest species. The map units of ecoregional meaning might facilitate new allocations for forest reproductive materials which are needed to increase genetic diversity. Furthermore, studies on genetic variability of forest species are required to understand the possible interactions between the ecological amplitude of forest species, their actual genetic diversity, and possible adaptation to future climate conditions.